Motivasi Siswa Mengikuti Ekstrakurikuler Olahraga Futsal di SMP Negeri Se-Kecamatan Talang Kelapa - Herlambang, M.; Wardiah, Dessy; Daryono, Daryono (ANTHOR: Education and Learning Journal, 2023)
The problem in this study was that many students did not attend extracurricular activities, were often lazy, talked a lot to themselves, and did not listen to the trainer's instructions during the training process. This study aims to find out how well the students' motivation at SMP Negeri 1 Talang Kelapa and students at SMP Negeri 2Talang Kelapa participate in extracurricular futsal. This type of research uses descriptive quantitative survey methods, the total population in this study is 30 students with a sample of 15 students at SMPN 1 Talang Kelapa and 15 students at SMPN 2Talang Kelapa, the instrument used is a questionnaire and the sampling technique isProbability Sampling is one of a sampling technique that provides equal opportunitiesfor each element (member) of the population to be selected as a member of the sample. The results of the research on the motivation of students to take part in Futsal Sports Extracurricular at State Junior High Schools in the Talang Kelapa District have a fairly good effect. 7 people at 23.4%, in the less category as much as 1 person at 3.0%.